Empirical Analysis of The Dynamic Interplay between Energy‎Consumption and Economic Growth in Nigeria - Ugwu, Kelechi Enyinna; Njoku , Charles Odinakachi; Otuonye , Anthony Ifeanyi; Nwaimo , Chilaka Emmanuel; Omeire , Edward Uche; Nwafor , Godwin Onyeka; Molukwu , Chuks Cornelius; Nwadike , Emmanuel Chijioke; Echeme , Ibeawuchi Ifeanyi; Onyeanwu, Chidi Christian; Anah , Cletus ‎Ikechukwu; Adeniyi , kolawole Ojo; et al. (International Journal of Accounting and Economics Studies, 2025)
The study investigated energy consumption and economic growth in Nigeria using time series data ‎for the period of 1986 to 2024. Energy consumption was measured by PMS consumption, ‎electricity consumption, coal consumption, and labour consumption, while economic growth was ‎measured by GDP per capita. The study used the Error Correction Model (ECM) to achieve its ‎objectives. The Johansen cointegration test showed that there was no long-run relationship ‎between the components of energy consumption and economic growth in Nigeria. In the short run, ‎it was observed that while PMS consumption and electricity consumption had an insignificant ‎effect on GDP per capita, coal consumption and labour consumption were significant to GDP per ‎capita growth. The study therefore recommended that the government should make adequate ‎provision to enhance electricity consumption towards boosting economic growth in the Nigerian ‎economy. This could be achieved if the federal government improves on energy generation, energy ‎transmission, and energy distribution to boost its consumption among economic agents such as ‎households, firms, markets, and the government itself‎.